Patient‐Reported Outcomes Are More Important Than Objective Inflammatory Markers for Sick Leave in Biologics‐Treated Patients With Rheumatoid Arthritis. Issue 11 (26th October 2018) - Olofsson, Tor; Söderling, Jonas K.; Gülfe, Anders; Kristensen, Lars‐Erik; Wallman, Johan K.
Abstract : Objective: To study the impact of common noncomposite disease activity measures on sick leave in biologics‐treated patients with rheumatoid arthritis (RA). Methods: Data from study visits by biologics‐treated RA patients of working age (<65 years) in the observational South Swedish Arthritis Treatment Group Register between 2005 and 2011, were included (5, 118 visits by 941 patients). We performed association analyses between various noncomposite disease activity measures at each visit and the number of days of sick leave during the subsequent month; this information was retrieved from the Social Insurance Agency. Adjusted separate generalized estimating equation regression models were used, and analyses were stratified according to sick leave status for the month preceding each visit (no, partial, or full sick leave). Results are presented as standardized beta coefficients for comparability. Results: Among modifiable noncomposite disease activity measures, patient's assessment of pain and disease activity scored on a visual analog scale (VAS) were most strongly associated with subsequent sick leave, irrespective of baseline sick leave status. Generally, measures that were more objective (swollen joint count, erythrocyte sedimentation rate, and C‐reactive protein) had less impact on sick leave compared with variables that were more subjective (patient's pain and global scores on a VAS, evaluator's global assessment of disease activity on a 5‐grade Likert scale, and tender joint count). Conclusion: Measures of disease activity that are more subjective have a greater impact on sick leave in biologics‐treated patients with RA compared with variables that are more objective, suggesting a stronger focus on subjective measures when targeting work loss or intervening to reduce it.